On The Adaptive Coefficient Scanning of JPEG XR / HD Photo - Testoni, Vanessa; Costa, Max H. M.; Kirovski, Darko; Malvar, Henrique S. (Data Compression Conference, 2010)
We explore several local and global strategies for adaptive scan ordering of transform coefficients in JPEG XR/HD Photo. This codec applies a global adaptive scan-order heuristic with respect to an effective localized predictor. The global ordering heuristic, although simple, performs as well as localized techniques that are computationally significantly more complex. We conclude that effective localized prediction not only minimizes but also essentially randomizes coefficient residuals, so that a global statistic is sufficient to deliver near-optimal compression performance.